Selectivity shifting behavior of Pd nanoparticles loaded zinc stannate/zinc oxide (Zn2SnO4/ZnO) nanowires sensors - Arafat, M.M.; Ong, Ji Yan; Haseeb, A.S. Md. Abdul (Elsevier, 2018)
In this research, the gas sensing behavior of Pd nanoparticles loaded zinc stannate/zinc oxide (Zn 2 SnO 4 /ZnO) nanowires were investigated. The Zn 2 SnO 4 /ZnO nanowires were grown on Au interdigitated alumina substrate by carbon assisted thermal evaporation process. Pd nanoparticles were loaded on the Zn 2 SnO 4 /ZnO nanowires by wet reduction process. The nanowires were characterized by X-ray diffractometer, field emission scanning electron microscope and energy dispersive X-ray spectroscope. The Zn 2 SnO 4 /ZnO and Pd nanoparticles loaded Zn 2 SnO 4 /ZnO nanowires were investigated for detecting H 2 , H 2 S and C 2 H 5 OH gases in N 2 background. Results revealed that the average diameter and length of as-grown Zn 2 SnO 4 /ZnO nanowires were 74 nm and 30 μm, respectively. During wet reduction process,Pd particles having size of 20–60 nm were evenly distributed on the Zn 2 SnO 4 /ZnO nanowires. The Zn 2 SnO 4 /ZnO nanowires based sensors showed selective response towards C 2 H 5 OH whereas Pd nanoparticles loaded Zn 2 SnO 4 /ZnO nanowires showed selective response towards H 2 . The recovery time of the sensors reduced with Pd loading on Zn 2 SnO 4 /ZnO nanowires. A mechanism is proposed to elucidate the gas sensing mechanism of Pd nanoparticles loaded Zn 2 SnO 4 /ZnO nanowires.